“O quê?” e o “Para quê?” do ensino de Religião na Escola e na Formação do Professor - Gilz, Claudino; Junqueira, Sérgio Rogério Azevedo (2007)
Opresente trabalho busca contribuir com o debate sobre “o quê?” e o “para quê?” do ensino de religião na escola e na formação do professor. Discorre sobre as luzes esombras do livro didáticoi na sua utilização diária em sala de aula pelo corpo docente e discente. Discute a pertinência do livro didático na implantação do modelo de Ensino Religioso inaugurado pela nova Lei de Diretrizes e Bases da Educação Nacional,nº 9.394/96. Apresenta um breve relato de uma pesquisa realizada com professores escritores e não-escritores de um livro didático de Ensino Religiosoii a respeito de aspectos,tais como: a concepção de educação, a concepção religiosa, o conteúdo, a metodologia e a linguagem.
The present work aims at contributing towards the debate about the “what” and “to what purpose” of religious teaching in schools and in teacher’s education. It expands on the lights and the shadows of didactic books and their daily utilization in the classroom by teachers and students alike. It discusses the pertinence of the didactic book in the implantation of Religious Teaching inaugurated by the new Guidelines and Bases for National Education number 9.394/96. It presents a brief account of a research project that took place among teachers, writers and nonwriters of a didactic book for Religious Teaching, touching on aspects such as: the concepts of education, religious concepts, content, methodology, and language.
Keywords: Classroom Manuals; Didactic Book; Ensino Religioso; Formação Docente; Livro Didático; Religious Teaching; Teacher’s Education